Analysis of Student Conformity Based on Gender Using the Rasch Model - Yull Reinita; Mega Iswari; Febri Wandha Putra (International Journal of Applied Counseling and Social Sciences, 2020)
This research is based on the phenomenon that occurs, namely there are still students who differentiate themselves based on the groups they associate with at school, causing some students to get into problems. This type of research is a comparative descriptive which aims to describe the differences in conformity based on the gender of the students. The population in this study were students of SMK class XI. The sampling technique in this research is to use random sampling technique. The instrument used was a Likert scale model and a questionnaire containing statements related to student conformity. Test the validity of the instrument using the Rasch Model. The data analysis technique used the Independent Sample t-Test. The results of the study found that there were differences in conformity between male and female students.